Implementasi Algoritma Boyer Moore Pada Aplikasi Kamus Istilah Kebidanan Berbasis Web - Rizky Ivan Darmawan; Anif Hanifa Setianingrum; Arini Arini (Program Studi Sistem Informasi, 2018)
The lack of understanding in obstetrics and limit of instructional media has become one of the factors in the making of dictionary application of midwifery. The current dictionary is still a thick book with many terms in it and difficult to use. dictionary midwifery terms have a weakness in the search process, because users should search for words and terms manually by opening pages per page on the dictionary and existing data could not be changed.Keywords: Algorithm, Boyer Moore, Midwifery Dictionary.